Association of Chronotypes and Sleep Disturbance with Perceived Job Stressors and Stress Response: A Covariance Structure Analysis - Miyama H (Dove Medical Press, 2020)
Hitoshi Miyama,1,2 Akiyoshi Shimura,1 Wataru Furuichi,1 Tomoteru Seki,1 Kotaro Ono,1 Jiro Masuya,1 Yuko Odagiri,3 Shigeru Inoue,3 Takeshi Inoue1 1Department of Psychiatry, Tokyo Medical University, Tokyo 160-0023, Japan; 2Department of Psychiatry, Maruyamasou Hospital, Ishioka, Ibaraki 315-0116, Japan; 3Department of Preventive Medicine and Public Health, Tokyo Medical University, Tokyo 160-8402, JapanCorrespondence: Akiyoshi ShimuraDepartment of Psychiatry, Tokyo Medical University, 6-7-1 Nishishinjuku, Shinjuku-Ku, Tokyo 160-0023, JapanTel +81-3-3342-6111Fax +81-3-3340-4499Email sim@tokyo-med.ac.jpBackground: Chronotype, which is a person’s circadian characteristics throughout a day, greatly influences a person’s lifestyle, health, and sleep pattern; however, the association between job stress and chronotype remains unknown to date. Therefore, in this study, we analyzed the effects of chronotype on the job stress response, and the mediating effects of sleep disturbance using path analysis.Methods: A cross-sectional survey was conducted on 535 adult volunteers (239 men and 296 women; average age, 41.2 ± 11.9 years) from the community. Participants were evaluated using the Diurnal Type Scale for chronotype, Pittsburg Sleep Quality Index for sleep disturbance, Brief Job Stress Questionnaire for job stressors, and the psychological and physical stress response (PPSR). To investigate the association between chronotype, sleep disturbance, perceived job stressors, and PPSR, a covariance structure analysis was performed.Results: The eveningness chronotype had a significant weak direct effect on sleep disturbance, perceived job stressors, and PPSR, and had a significant indirect effect through sleep disturbance. The perceived job stressors indirectly increased PPSR through sleep disturbance. Sleep disturbance mediated the effects of the eveningness chronotype and perceived job stressors on PPSR. This model accounted for 37.3% of the variability in PPSR of adult workers.Conclusion: Chronotype affected PPSR through sleep disturbance. Therefore, improving the sleep disturbance of workers with the eveningness chronotype may reduce their stress response.Keywords: eveningness chronotype, sleep disturbance, job stress, Diurnal Type Scale